WOMEN AND WORK MOBILITY : SOME DISQUIETING EVIDENCES FROM THE INDIAN DATA - Mridul Eapen (Centre for Development Studies-WP358, 2004)
In this paper we have attempted to raise an issue which has always concerned feminist scholars- the sex segregation of jobs and its perpetuation over time to the disadvantage of women workers, in the context of the nineties, the period of globalisation in India. Our data show that horizontal segregation indicated by the index of dissimilarity has declined during the period 1987-88 and 1993-94 in urban areas but has increased slightly in rural areas. Given the aggregate nature of the data, the indices are very low. Women are more mobile between establishments while hardly achieving any upward mobility in terms of status/occupation. More importantly, we emphasise the need to include women's domestic work as a category of work in such an economic analysis, arguing that a growing proportion of women (or `working' days of women) moving into the activity `not in the labour force' whether voluntary or involuntary, reduces their mobility. It tends to enhance women's dependence, making them economically vulnerable and hence weakens their `bargaining position' within the household and outside it. Unlike men, for whom the need to find employment is clearly central, for women full time domesticity is not regarded as `unnatural'. Our attention was drawn sharply in this direction based on recent female work participation data for Kerala, macro and micro, suggesting a `voluntary' withdrawal of women from the labour force. The state boasts of the high(est) female literacy rates among all states of India; yet as recent studies have shown it scores poorly in terms of what are termed as non-conventional indicators attempting to capture power and subordination